Applying Artificial Intelligence in Project Management: A Practitioner’s Perspective - Aleksandravičiūtė, Greta (Vilnius University Open Series, 2025)
Organizations are deploying Artificial Intelligence (AI) solutions to manage project processes efficiently. Research shows that the potential of AI is growing. It is predicted that, by 2030, 85% of project tasks will be performed by using AI, thereby improving the project success rate to 25% (Nieto-Rodríguez & Vargas, 2023).The aim of this research paper is to analyze the characteristics of the application of AI in project activities. To achieve this goal, the following objectives are formulated: (1) to analyze the applicability of AI in project management, (2) to identify the benefits of AI in project activities, and (3) to investigate the current situation of the integration of AI in project management processes.To achieve the aim and objectives of this work, complex research methods are applied. For the presentation of the theoretical part of the project, systematic and comparative analysis of foreign scientists’ works is used. The exploratory research is carried out by employing a questionnaire survey.The results of the study show that AI is applied in project planning and implementation phases in resource planning, scheduling tasks, and risk management. AI allows planning and controlling project progress and risks based on current and retrospective data. The application of AI allows for a more accurate prediction of results and optimized decision making. Organizations face barriers in terms of the application of AI, such as lack of staff skills, insufficiently prepared infrastructure, and undefined legal and ethical issues surrounding the use of AI, which slows down the scalability of artificial intelligence.
Keywords: project management; rtificial intelligence; artificial intelligence usage; artificial intelligence benefits